THE ROLE OF CORRUPTION EDUCATION IN COMBATING CORRUPTION CRIMES IN THE FUTURE - Ina Heliany; Erwin Asmadi; Humala Sitinjak; Arief Fahmi Lubis (Jurnal Pembaharuan Hukum, 2023)
To reduce corruption in the future, of course, it is necessary to provide anti-corruption education from now on, because education and public awareness are also important components in fighting corruption. The purpose of this paper is to analyze corruption education in combating corruption crimes in the future and handling corruption and anti-corruption education in various countries. The type of research used in this research is normative juridical. Normative juridical research is research that uses the legis positivist conception. Anti-corruption education in the future must be instilled in an integrated manner from primary to tertiary education Anti-corruption education in the future must be instilled in an integrated manner from primary to tertiary education. It is hoped that through education about anti-corruption from an early age, it can create a person who has a more introspective personality, so that when it is time to enter society, children are no longer easily influenced and have sufficient and correct knowledge about anti-corruption. Learning from China, Indonesia should also be able to fight corruption and eradicate this chronic disease from the country. In addition to a strong commitment from the country's leaders and law enforcers, China-style corruption eradication may be applicable in Indonesia. The preventing corruption through education in Indonesia and Malaysia is almost the same, namely through the internalization of anti-corruption values into certain subjects, while Singapore emphasizes more on character education.